2008
DOI: 10.1177/1534765608319082
|View full text |Cite
|
Sign up to set email alerts
|

The emotional impact on and coping strategies employed by police teams investigating internet child exploitation.

Abstract: Work on Internet child exploitation (ICE) teams require individuals to perform a number of investigative tasks, including viewing graphic images and videos of young children being sexually assaulted and tortured, to identify victims and locate perpetrators. Individuals involved in this work may be at higher risk for experiencing secondary traumatic stress because of the graphic images and sounds to which they are exposed. The impact of ICE investigations and what helps and hinders coping with the work was expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
177
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(210 citation statements)
references
References 29 publications
16
177
1
16
Order By: Relevance
“…Two existing studies of child pornography investigators include discussions of secondary trauma but the studies are qualitative in nature (Burns et al 2008;Stevenson 2007) and do not actually assess whether investigators are suffering from STSD. Burns et al (2008) interviewed 14 Internet child pornography investigators from the Royal Canadian Mounted Police using the critical incident method.…”
Section: Negative Effects Of Exposure To Disturbing Mediamentioning
confidence: 98%
See 1 more Smart Citation
“…Two existing studies of child pornography investigators include discussions of secondary trauma but the studies are qualitative in nature (Burns et al 2008;Stevenson 2007) and do not actually assess whether investigators are suffering from STSD. Burns et al (2008) interviewed 14 Internet child pornography investigators from the Royal Canadian Mounted Police using the critical incident method.…”
Section: Negative Effects Of Exposure To Disturbing Mediamentioning
confidence: 98%
“…Two existing studies of child pornography investigators include discussions of secondary trauma but the studies are qualitative in nature (Burns et al 2008;Stevenson 2007) and do not actually assess whether investigators are suffering from STSD. Burns et al (2008) interviewed 14 Internet child pornography investigators from the Royal Canadian Mounted Police using the critical incident method. The authors identified a number of negative outcomes reported by these investigators including a greater awareness of the scope of Internet child exploitation, physical and emotional symptoms, intrusive thoughts about cases while not at work, stigma, isolation from others who could not understand the investigators' work, an inability to discuss the investigators' work for fear of traumatizing other people, concerns about and reliance on other team members, and an increased protectiveness of their own and other children.…”
Section: Negative Effects Of Exposure To Disturbing Mediamentioning
confidence: 98%
“…Badania w grupie oficerów policji wykazały też, że powstrzymywanie się od zaangażowania emocjonalnego w sprawy śledz-twa pozwala efektywnie funkcjonować i skupiać się na zakładanym celu sprawy oraz redukować ryzyko stresu pourazowego [25].…”
Section: Omówienieunclassified
“…Some practitioners also can use techniques such as informal debriefings with colleagues to reduce stress following interviews (Ahern 2016a). Other strategies for practitioners investigating on-line images included preparing themselves mentally (Burns 2008 It appears from studies that police officers are finding themselves in the uncomfortable and stressful position of being expected or expecting to manage their emotions in situations that are psychologically demanding. The simultaneous demands of maintaining an unemotional response to human anguish and abusive behaviour, simultaneously trying to demonstrate empathy to the victims of child abuse, can place the police officer in situations of great emotional distress.…”
Section: Child Protection Policing: Implications For Police Officersmentioning
confidence: 99%